Adsorption and desorption of copper in paddy field soil in Merlimau, Melaka / Mohd Akmal Jamal - Jamal, Mohd Akmal (Faculty of Plantation and Agrotechnology, 2018)
Copper(Cu) is a red-brown metal and the chemical element of atomic number 29. Copper is essential involved in many process in plant that are exist in multiple oxidation state in vivo. Adsorption and desorption should be able done by plant so that plant will get enough nutrient. Copper is an essential micro nutrient that needed by paddy. Copper needed in paddy growth and yield formation of the rice. (Wang, 2008). So, copper can be classified as the important nutrient on paddy development and production. Even though copper had enough in the soil, the problem will be occur in the soil where the ability of the soil in adsorption and desorption of Cu to being uptake by the plant The sample had been taken at 3 places in Jasin, there are Tengah Padang, Pengkalan Samak and Sungai Rambai. The result show that the sample at Sungai Rambai seem had good soil compared to Pengkalan Samak and Tengah Padang. Because the result shows that organic matter content at Sungai Rambai higher than Pengkalan Samak and Tengah Padang. To define the rate of adsorption and desorption of the (Cu), by using the bacth method, 7 concentration of copper chloride had been used. Then by using Freundlich and Langmuir Model, we can define the rate of (Cu) adsorption and desorption